Genome-Wide Assessment of a Korean Composite Pig Breed, Woori-Heukdon - Kim, Yong-Min; Seong, Ha-Seung; Kim, Young-Sin; Hong, Joon-Ki; Sa, Soo-Jin; Lee, Jungjae; Lee, Jun-Hee; Cho, Kyu-Ho; Chung, Won-Hyong; Choi, Jung-Woo; Cho, Eun-Seok (Frontiers in Genetics, 2022)
A Korean synthetic pig breed, Woori-Heukdon (WRH; F3), was developed by crossing parental breeds (Korean native pig [KNP] and Korean Duroc [DUC]) with their crossbred populations (F1 and F2). This study in genome-wide assessed a total of 2,074 pigs which include the crossbred and the parental populations using the Illumina PorcineSNP60 BeadChip. After quality control of the initial datasets, we performed population structure, genetic diversity, and runs of homozygosity (ROH) analyses. Population structure analyses showed that crossbred populations were genetically influenced by the parental breeds according to their generation stage in the crossbreeding scheme. Moreover, principal component analysis showed the dispersed cluster of WRH, which might reflect introducing a new breeding group into the previous one. Expected heterozygosity values, which were used to assess genetic diversity, were 0.365, 0.349, 0.336, 0.330, and 0.211 for WRH, F2, F1, DUC, and KNP, respectively. The inbreeding coefficient based on ROH was the highest in KNP (0.409), followed by WRH (0.186), DUC (0.178), F2 (0.107), and F1 (0.035). Moreover, the frequency of short ROH decreased according to the crossing stage (from F1 to WRH). Alternatively, the frequency of medium and long ROH increased, which indicated recent inbreeding in F2 and WRH. Furthermore, gene annotation of the ROH islands in WRH that might be inherited from their parental breeds revealed several interesting candidate genes that may be associated with adaptation, meat quality, production, and reproduction traits in pigs.